Monsters, zombies + addicts : poems - Zepeda, Gwendolyn (Arte Público Press, 2015)
"I was scared of a thing that might have happened. In daytime I m sure it / never did. At night, I don t trust daylit memories or instincts. In nightmares, like / filmstrips, the feared thing occurs." In her second poetry collection, monsters real and imagined chase Houston Poet Laureate Gwendolyn Zepeda through late nights when she can t sleep. Ghosts routinely visit in the early morning hours, but in spite of her fears, she dares to believe that she has escaped the devils that once followed her. This collection of 62 narrative poems contains witty observations about the rituals of contemporary life. In "Cocktail Hours", she wonders, "What if all my nights were Christmas lights on patios with tinkling drinks /and fun conversations." And in "Recipe for Fun," Zepeda offers a ten-point guide to soothing away life s frustrations, including a suggestion to get some peace by giving "everyone in your house pizza, cat food or video games." Musings on family, remembrances of childhood games and encounters with strangers (and ants!) fill this clever, thought-provoking collection in which Zepeda dares to express her individuality. She knows that she is different, "Maybe I am a boy in drag. / Especially here, where I don t feel like / everybody else." She doesn t follow others blindly or do what society expects of her. Readers will appreciate this second poetry collection, which is deeply personal yet universal in its hopes and fears.